2016
DOI: 10.1111/1750-3841.13443
|View full text |Cite
|
Sign up to set email alerts
|

Release Kinetics of Nisin from Chitosan–Alginate Complex Films

Abstract: Understanding the release kinetics of antimicrobials from polymer films is important in the design of effective antimicrobial packaging films. The release kinetics of nisin (30 mg/film) from chitosan-alginate polyelectric complex films prepared using various fractions of alginate (33%, 50%, and 66%) was investigated into an aqueous release medium. Films containing higher alginate fractions showed significantly lower (P < 0.05) degree of swelling in water. Total amount of nisin released from films into an aqueo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 29 publications
(35 reference statements)
1
14
0
Order By: Relevance
“…CHI is a popular biomaterial for edible film and coating production [ 6 ]. Because of its biocompatibility, antimicrobial activities, low oxygen permeability, and good mechanical properties, CHI has been combined with other hydrocolloids such as starch, gelatin, and alginate to produce blended or multi-layered films [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…CHI is a popular biomaterial for edible film and coating production [ 6 ]. Because of its biocompatibility, antimicrobial activities, low oxygen permeability, and good mechanical properties, CHI has been combined with other hydrocolloids such as starch, gelatin, and alginate to produce blended or multi-layered films [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Some antioxidative substances or bioactive compounds such as essential oil, ferulic acid, maqui berry and polyphenols from thyme extracts can be added to the starch-incorporated lm to limit its disadvantages. 7,[10][11][12] Based on the incorporation methods, sustained-release chitosan lm with medicine release or enhanced fresh-keeping ability [13][14][15][16] can be developed. Although the chitosan complex lm can exhibit multiple functions depending upon the incorporation method, the use of chitosan has been seriously restricted because of its poor solubility.…”
Section: Introductionmentioning
confidence: 99%
“…However, the lamination of the PLA film to the SSP film significantly decreased the WVP to 0.91 ± 0.16 × 10 −9 g m/m 2 s Pa, which is similar to the PLA film alone. It has been reported that multilayer (PLA/fish skin gelatin/PLA) and bilayer (fish skin gelatin/PLA) films exhibited decreases in the WVP by laminating PLA to gelatin films (Hosseini et al., ; Lee & Song, ). Soy protein isolate and PLA‐laminated films also had decreases in the WVP with increasing PLA concentrations (González & Igarzabal, ; Rhim et al., 2017).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the SSP and PLA layer were tightly attached without a layer boundary, likely because of the molecular interactions between SSP and PLA (González & Igarzabal, 2013). The molecular interactions between biopolymers could be further elucidated by other methods, such as FTIR and isothermal titration calorimetry (Chandrasekar et al, 2016;Chandrasekar, Coupland, & Anantheswaran, 2017). It has been suggested that the physical properties of biopolymer films can be improved by laminating with PLA (González & Igarzabal, 2013;Rhim, Lee, & Ng, 2007).…”
Section: Physical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation